Researching the prospects for change that COVID disruption has brought to high stakes testing and accountability systems - Moss, Gemma (Education Policy Analysis Archives, 2022)
This paper explores the disruption that COVID has brought to the normal functioning of performance-based accountability systems and asks whether this has created new possibilities for those organising against the use of high stakes testing in education. Drawing on a sequence of research projects exploring primary schools’ responses to the pandemic in England during 2020-21, this article considers the ways in which the pandemic creates new conditions for dismantling high stakes testing and accountability regimes, and the role of research in making the case for change.